Examining the Effect of Political Connections, and Managerial Ability on the Relationship between Audit Quality and Information Asymmetry - Sahel Abaszade; HamidReza Ganji (پژوهش‌های تجربی حسابداری)
The purpose of this study is to examining the effect of political connections, and managerial ability on the relationship between audit quality and information asymmetry. Therefore, thre hypotheses were formulated to achieve the study objectives. Then, data from 132 firms (observation) listed on the Tehran Stock Exchange during 2015-2022 were collected and analyzed using the Eviews software. The results of the study showed that auditor quality has a negative and significant relationship with information asymmetry. Political connections do not moderate the relationship between audit quality and information asymmetry. but Managerial ability moderates the relationship between audit quality and information asymmetry. This study is distinguished from other studies by helping to expand the boundaries of knowledge, raise new questions for future research, and provide practical solutions to existing problems, and provides practical suggestions to policymakers and investors